Ontogénesis de la morfología verbal búlgara, etapas iniciales - Попова Beлкa (Eslavística Complutense, 2005)
The Article studies the early verb development and demarcation of stages in six Bulgarian-speaking children. This Approach is based on naturalness theory (the model of Natural Morphology). The longitudinal data corpus has been processed by CLAN - a programme package of the CHILDES system.